Sidney Webb and equal pay, 1891 (1891)
1891 1880-1914 "Sidney Webb and equal pay, 1891" [EP0075b], 1891 This article published in the October 1891 issue of The Women's Trade Union Review, published by the Women's Trade Union League, reports on a paper given by Sidney Webb on the 'Difference in wages paid to men and women'. Webb does not appear to support the rate for the job, stating women often produce inferior work, require a lower standard or living and often only work for 'pocket money'.